Herding trend in working capital management practices: Evidence from the non-financial sector of Pakistan - Umar Farooq; Mosab I. Tabash; Ahmad A. Al-Naimi; Linda Nalini Daniel; Mohammad Ahmad Al-Omari (Journal of Risk and Financial Management, 2023)
Working capital management requires careful attention from corporate managers because it plays an important role in corporate stability. The social belongingness of managers induced them to learn from their society, colleagues, and overall industrial movement. They also learn from their peers that have more strategic efficiency. In line with these arguments, the objective of the current study is to explore the peer influence on corporate working capital management practices. For regression analysis, we utilized ten years of data (2009-2018) of non-financial publicly listed firms at PSX (Pakistan Stock Exchange). We used the cash conversion cycle (CCC) as a proxy variable to measure working capital management (WCM). We employed panel fixed effect and system GMM (generalized method of moments) models to estimate regression between the variables of the study. The empirical findings suggest the significant impact of peer WCM on corporate WCM. They also suggest the significant impact of other variables that determine the WCM. This study recommends social learning policy for corporate managers. They can learn from their peers to manage the working capital. Most previous studies discuss peer influence on investment decisions, corporate cash holding, financing policy, etc., but no study explores such a relationship specifically in the case of Pakistan.
Keywords: G31; G41; 650; cash conversion cycle; macro-economic factors; peer influence; working capital management